2023
DOI: 10.1111/tid.14036
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the INCREMENT‐SOT‐CPE score in a large cohort of liver transplant recipients with carbapenem‐resistant Enterobacterales infection

Abstract: Background Management of infections due to carbapenemase‐resistant Enterobacterales (CRE) in solid organ transplant (SOT) recipients remains a difficult challenge. The INCREMENT‐SOT‐CPE score has been specifically developed from SOT recipients to stratify mortality risk, but an external validation is lacking. Methods Multicenter retrospective cohort study of liver transplant (LT) recipients colonized with CRE infection who developed infection after transplant over 7‐year period. Primary endpoint was all‐cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A more recent, large, multicenter, international cohort study [ 92 ] reported that among 840 CRE carriers, 29.8% developed a CRE infection within 30 days post-LT; distributed as BSI (36.5%), SSI (26%), and lower respiratory tract infections (23.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent, large, multicenter, international cohort study [ 92 ] reported that among 840 CRE carriers, 29.8% developed a CRE infection within 30 days post-LT; distributed as BSI (36.5%), SSI (26%), and lower respiratory tract infections (23.6%).…”
Section: Resultsmentioning
confidence: 99%
“…A mortality risk score to predict 30-day mortality (INCREMENT-SOT-CPE [ 94 ]) was developed and validated [ 92 ]. The INCREMENT-SOT-CPE [ 8 ] score takes in consideration INCREMENT-CPE mortality score ≥8, no source control, inappropriate empirical therapy, cytomegalovirus disease, and lymphopenia.…”
Section: Resultsmentioning
confidence: 99%
“…As toxicity is not a major concern, current restrictions for the incorporation of this and other new antimicrobials in empirical schemes are mainly supported by the aim of the protection of these new precious alternatives against the emergence of multirresistance in the grounds of antibiotic stewardship programs. 1,7 In the study of Rinaldi et al, 8 the INCREMENT-SOT score is a subject of external validation in liver transplant recipients with different types of infections due to CPE. The INCREMENT-SOT score was designed as a tool that could aid in the selection of SOT recipients with CPE bloodstream infections with the highest risk of 30-day mortality and, therefore, candidates the best available combination therapies when infection is suspected.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…In the study of Rinaldi et al., 8 the INCREMENT‐SOT score is a subject of external validation in liver transplant recipients with different types of infections due to CPE. The INCREMENT‐SOT score was designed as a tool that could aid in the selection of SOT recipients with CPE bloodstream infections with the highest risk of 30‐day mortality and, therefore, candidates the best available combination therapies when infection is suspected 9 .…”
mentioning
confidence: 99%